2022
DOI: 10.5005/jp-journals-10080-1533
|View full text |Cite
|
Sign up to set email alerts
|

Open Reduction and Internal Fixation Using Double Plating with Biological and Artificial Bone Grafting of Aseptic Non-unions of the Distal Humerus: Clinical Results

Abstract: A bstract Aim Intra-articular non-union of fractures is an uncommon but complex problem because in general, it is characterised by marked instability, pain, strength loss and significant functional limitation. The aim of this study is to report our prospective medium-term outcomes of the treatment of intra-articular, distal humeral aseptic non-unions using open reduction and internal fixation, augmented with artificial bone. Materials and methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The results of a retrospective case series study aimed at evaluating the success of open reduction and internal fixation using double plating with biological and artificial bone grafting on 16 patients with aseptic nonunions of the distal humerus showed that after hardware failure or biological constraints, the use of two locking plates and bone graft augmentation using autografts or allografts with artificial bone grafts is an effective treatment for intra-articular distal humeral nonunions 19 . Another study investigated the plate-and-bone-strut-allograft method with bone chip augmentation in third humeral shaft aseptic nonunions.…”
Section: Discussionmentioning
confidence: 99%
“…The results of a retrospective case series study aimed at evaluating the success of open reduction and internal fixation using double plating with biological and artificial bone grafting on 16 patients with aseptic nonunions of the distal humerus showed that after hardware failure or biological constraints, the use of two locking plates and bone graft augmentation using autografts or allografts with artificial bone grafts is an effective treatment for intra-articular distal humeral nonunions 19 . Another study investigated the plate-and-bone-strut-allograft method with bone chip augmentation in third humeral shaft aseptic nonunions.…”
Section: Discussionmentioning
confidence: 99%
“…Current evidence on the assessment of outcomes in proximal or distal joint stiffness in intra-articular non-union fractures, treated with open reduction and internal fixation augmented with artificial bone, shows good outcomes in terms of muscle strength, rate of return to work, and function, as assessed by the Mayo Elbow Performance Score and Oxford Elbow Score. 28 , 29 In addition, studies have reported that surgical treatment can restore the structural stability of the joint and soft-tissue structure in an injury with dislocation or subluxation. 29–32 …”
Section: Discussionmentioning
confidence: 99%
“…28 , 29 In addition, studies have reported that surgical treatment can restore the structural stability of the joint and soft-tissue structure in an injury with dislocation or subluxation. 29–32 …”
Section: Discussionmentioning
confidence: 99%